Analysing the behaviour of academic collocations in a corpus of research-papers: A data-driven study - Pinto, Paula Tavares [UNESP]; De Camargo, Diva Cardoso [UNESP]; Serpa, Talita [UNESP]; Da Silva, Luciano Franco [UNESP] (Faculdade de Letras da UFMG, 2021)
Authors from different countries have published their papers in English, aiming to promote their research results widely and to become internationally known by their peers. It is also true that, although they are aware of the English terminology used in their respective field, some authors still struggle with some features of academic writing such as collocations. Thus, this paper presents a discussion on the underuse and overuse traces of academic collocations by Brazilian authors who had their articles published in English on an open electronic library of scientific journals. In order to analyse the collocations used by these researchers, we compiled a 906,035- word corpus from eight different academic areas. The collocations observed were statistically compared to those from an academic corpus of English writings which contains texts produced by English-speaking authors. Results showed that there are more collocations underused than overused by the authors. The analysis proved that the collocation repertoire of researchers could be broadened by being pointed out during academic writing workshops.
Analisando o comportamento de colocações acadêmicas em um corpus de artigos científicos: Um estudo dirigido por dados
Keywords: Academic collocations; Corpus linguistics; Research paper writing